Use of ultrasound in image-guided high-dose-rate brachytherapy: enumerations and arguments - Banerjee, Susovan; Kataria, Tejinder; Gupta, Deepak; Goyal, Shikha; Bisht, Shyam Singh; Basu, Trinanjan; Abhishek, Ashu (Journal of Contemporary Brachytherapy, 2017)
Inherently, brachytherapy is the most conformal radiotherapeutic technique. As an aid to brachytherapy, ultrasonography (USG) serves as a portable, inexpensive, and simple to use method allowing for accurate, reproducible, and adaptive treatments. Some newer brachytherapy planning systems have incorporated USG as the sole imaging modality. Ultrasonography has been successfully used to place applicator and dose planning for prostate, cervix, and anal canal cancers. It can guide placement of brachytherapy catheters for all other sites like breast, skin, and head and neck cancers. Traditional USG has a few limitations, but recent advances such as 3-dimensional (3D) USG and contrast USG have enhanced its potential as a dependable guide in high-dose-rate image-guided brachytherapy (HDR-IGBT). The authors in this review have attempted to enumerate various aspects of USG in brachytherapy, highlighting its use across various sites.